Risk factors of superficial surgical site infection post debridement and internal fixation of open fractures in long bones at Sanglah General Hospital, Bali, Indonesia - Stedy Adnyana Christian; Putu Astawa; I Ketut Suyasa (Intisari Sains Medis, 2021)
Background: The fracture condition exposed to the environment can damage muscle, vascular, and nerve tissue due to infection. This study aims to determine whether age, Hb, OF grade II, duration and surgery time are risk factors of superficial surgical site infection for post-debridement and internal fixation in long bone fractures.Methods: This study used cohort retrospective. Samples of patients with open long bone fractures at Sanglah Denpasar from February to July 2020 were assessed for their risk factors for infection based on secondary data from medical records, physical and laboratory examinations. Monitoring for infection incidence was performed 1-4 weeks postoperatively, based on clinical and infection markers (Procalcitonin). After that, descriptive and inferential statistical analysis was performed using the Chi-square test and Logistic Regression using SPSS version 24 for Windows.Results: Hb level < 10 g/dLwas proven to be a risk factor (p=0.027). There was a significant difference in patients with grade II  (p=0.049; RR=10.00). There was a significant difference in the risk with patients with surgery duration ? 2 hours (p=0.011; RR=15). There was a significant difference in the patients with time to operation ? 12 hours (p=0.005; RR=8). Logistic Regression Test proves that the most influencing factor for superficial surgical site infection is operation duration (RR=9.328).Conclusion: Hb, OF grade II, duration, and time to operation are risk factors of superficial surgical site infection for post-debridement and internal fixation in open fractures of the long bone. The most important risk factor for superficial surgical site infection is the duration of surgery.